Reproductive Health Issues and the Use of Ethnomedical Practices by the Various Communities and Tribes of Assam (International Journal of Food and Nutritional Sciences, 2022)
India is well known for its traditional system of medicine- Ayurveda, Siddha and Unani. These medicinal systems are found to be mentioned in the Vedas and ancient scriptures. Northeast India is home to about 225 tribal communities which comprises of about one third of the listed tribes of India and represents one of the biodiversity hotspots of the World. The tribes have the vast knowledge of medicinal plants and animals which are used by the local communities to treat various reproductive health issues. The present study focuses on the ethnomedical practices of various tribes and communities of Assam which are found to be very useful in treating the reproductive health issues of women .In the present investigation, a total of 43 species of plants were reported as having ethno-medicinal importance and used by local communities to cure different diseases. The documentation of the ethnomedicinal flora, and repatriation of the knowledge to the future generation is very important or else this orally transmitted knowledge might get lost in the near future.